Adsorption, desorption and persistence of fomesafen in soil. Issue 1 (27th August 2018) - Li, Xiao; Grey, Timothy; Price, Katilyn; Vencill, William; Webster, Theodore
Abstract: BACKGROUND: Fomesafen provides control of glyphosate‐resistant Palmer amaranth in cotton but frequent seedling injury has been reported. This study evaluated soil adsorption, desorption, and field persistence of fomesafen. RESULTS: The Freundlich distribution coefficient ( K f ) for fomesafen on seven US soils varied from 1.30 to 9.28 µg 1–1/ n g −1 mL 1/ n . The pesticide distribution coefficient ( K d ) and soil organic carbon normalized adsorption coefficient ( K OC ) varied from 1.11 to 12.76 mL g −1 and 58 to 1467 mL g −1, respectively. The soils evaluated had desorption rates of 11.06% to 81.31% after a single desorption cycle. Soil pH, organic matter, sand, silt and clay content had a significant impact on fomesafen adsorption and desorption. Fomesafen field half‐lives (DT50 ) in Cecil sandy loam were 47 and 34 days, compared with 6 and 4 days in Tifton loamy sand when fomesafen was applied at 1× and 2× the label rate, respectively. The fomesafen dissipation rate decreased significantly under low‐density polyethylene (LDPE) mulch compared with bare ground. CONCLUSION: Fomesafen soil adsorption to soils was not strong and was affected by multiple soil properties. Fomesafen field persistence varied significantly between soil types and under ground cover. The data suggest that soils with a lower pH and higher clay content are less likely to produce crop injury due to greater fomesafen adsorption. © 2018 Society of Chemical Industry Abstract : Fomesafen injury to sensitive crops such as cotton is frequently reported by farmers. This article presents information regarding fomesafen adsorption, desorption from soils and its soil persistence under field conditions.